In-vitro and In-vivo Antiasthmatic Studies of Ailanthus excelsa Roxb. on Guinea Pigs - Kumar, D.; Bhujbal, S. S.; Deoda, R. S.; Mudgade, S. C (Journal of Scientific Research, 2009)
Methanolic extract of stem barks of Ailanthus excelsa Roxb. was evaluated for antiasthmatic activity by employing in-vivo and in-vitro screening models in Guinea pigs. The results revealed that the methanolic extract produced significant dose-dependent antiasthmatic activity. Keywords: Mahanimb; Antiasthmatic activity; Histamine induced bronchoconstriction. © 2010 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. DOI: 10.3329/jsr.v2i1.2740 J. Sci. Res. 2 (1), 196-202 (2010)